Modifiable Coronary Risk Factors and Global Cardiovascular Risk - Julio Armando Sánchez Delgado; Nailé Edita Sánchez Lara (Revista Finlay)
Background: cardiovascular diseases are the most common, serious and risky diseases in terms of mortality and morbidity in much of the world. They are a preventable health problem taken into account the risk factors. Objective: to characterize the modifiable risk factors epidemiology and global cardiovascular risk. Method: a descriptive, retrospective, case series study was carried out. The universe included the individuals who attended the cardiology consultation belonging to the César Fornet Fruto University Polyclinic health area of the Banes municipality, Holguín province, during June-December 2020. By simple random sampling, sixty-seven individuals who fulfilled the inclusion/ exclusion criteria were choosen. The studied variables were: age, sex, smoking, obesity, arterial hypertension, diabetes mellitus. A questionnaire designed for the purposes of the study was applied. The Chi Square calculation, Odds Ratio, recurrence risk allowed estimating the association between variables, the magnitude of the association and the recurrence of the event. Results: the 50-59 and 70-79 age groups represented the 26.9 % each, predominantly female (58.2 %). Hypertension (X2 = 20.7 OR = 54.3 95 % CI [19.14; 154]), diabetes mellitus (X2 = 10 OR = 5.52 95 % CI [2.63, 11.57]) and smoking (X2 = 3.8 OR = 2.8 95 % CI [1.4; 5.68]), determined the occurrence and probability of cardiovascular disease and showed a predominant incidence and risk of occurrence. The coexistence of three or more risk factors affected 29 individuals (43.2 %) and expressed a higher risk (RR = 0.76 IC95 % [0.54, 1.07]). Cardiovascular risk classified as moderate (34.3 %) and low (25.3 %). Conclusions: cardiovascular risk is determined by multiple modifiable risk factors.